2014
DOI: 10.4103/0976-237x.137946
|View full text |Cite
|
Sign up to set email alerts
|

Oral lichen planus and stress: An appraisal

Abstract: Introduction:Oral lichen planus (OLP) is a chronic inflammatory disease characterized by bilateral white striations or plaques on the buccal mucosa, tongue or gingiva that has a multifactorial etiology, where the psychogenic factors seem to play an important role.Purpose:The aim of this study was to determine the existing relation between the OLP and psychological alterations of the patient, such as stress, anxiety, and depression.Materials and Methods:Hospital anxiety and depression scale was applied for psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 11 publications
1
38
0
2
Order By: Relevance
“…Emerging evidences are suggesting that psychogenic factors such as anxiety, depression, and stress play important roles in the onset and progression of OLP . A high salivary cortisol level positively correlated anxiety was also showed in patients with OLP .…”
Section: Discussionmentioning
confidence: 88%
“…Emerging evidences are suggesting that psychogenic factors such as anxiety, depression, and stress play important roles in the onset and progression of OLP . A high salivary cortisol level positively correlated anxiety was also showed in patients with OLP .…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies have suggested that OLP is a T cell-mediated autoimmune disease (3,12). Particular tendencies, such as smoking, alcohol consumption, drugs, eating spicy foods and bad hygiene, may exasperate symptoms of OLP (3,4,6). In addition, psychological disorders, such as anxiety, depression and stress, are associated with OLP (3,6,13).…”
Section: Discussionmentioning
confidence: 99%
“…(8). Histologically, OLP is characterized by a dense band-like lymphocytic infiltrate in the immediate sub-epithelial region with basal epithelial cell destruction (6).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Topical antimycotics (e.g., nystatin and amphotericin) may be prescribed when an infection is present. [3] Erosive OLP that is recalcitrant to topical corticosteroids may respond to topical tacrolimus. [4] Other potential therapies for recalcitrant OLP include hydroxychloroquine, dapsone, systemic corticosteroids, and topical and systemic retinoids.…”
Section: Introductionmentioning
confidence: 99%